How do good teachers teach? Bases and values - Silvia Branda; María Cristina Martínez; Luis Porta (Universidad de Granada, 2013)
There are certain basis in teaching that already exist before the actual teaching takes place. These bases are not the result of classroom practices or the use of methods or techniques, they are part of the necessary requirements for the act of teaching something to someone. These bases are not the components of a recipe or a set of rules that we have to use mechanically. They are the guidelines, criteria, perspectives, options, points of view that make teaching and learning meaningful. In this paper we analyze an interview carried out with a "memorable teacher" to find out the grounds, perspectives and options from those teachers who have left a deep mark in their students. Even though many teachers are seeking a list of tips, tools or methods to face their classes, we are not offering any. We are just analyzing hints, gestures or traces, what Fried (1995:47) calls "the connection between passion for teaching and quality learning".